Composite pole piece, preparation method thereof and solid-state battery

By introducing a solid electrolyte layer with multiple holes on the surface and a first active material layer covering these holes in the composite electrode sheet of the solid-state battery, combined with the current collector layer, the problem of large interface resistance during fast charging of the solid-state battery is solved, and the fast charging and cycling performance of the battery is significantly improved.

CN119864361APending Publication Date: 2025-04-22BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905591.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

During the fast charging process of solid-state batteries, due to the large interface resistance between the solid-state electrolyte and the positive and negative electrodes, the energy loss increases and the cycling performance of the battery is reduced.

Method used

A composite electrode sheet is adopted, which includes a solid electrolyte layer, a first active material layer and a current collector layer. A plurality of holes are distributed on the surface of the solid electrolyte layer. The first active material layer covers these holes. The current collector layer is arranged on the side of the first active material layer away from the solid electrolyte layer. The composite electrode sheet is prepared by laser lactation and other methods to increase the surface area of ​​the solid electrolyte and improve the contact area and bonding strength between the active substance and the solid electrolyte.

Benefits of technology

It effectively reduces the interface contact resistance between the solid electrolyte and the positive and negative electrodes, improves the fast charging and cycling performance of the battery, and ensures stable transmission of ions between the electrode and the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864361A_ABST
    Figure CN119864361A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a composite pole piece, a preparation method thereof and a solid-state battery. The composite pole piece comprises a solid electrolyte layer, a first active substance layer and a current collector layer, a plurality of holes are distributed in the surface of at least one side of the solid electrolyte layer, the first active substance layer is arranged on one side of the solid electrolyte layer, the first active substance layer covers the holes, and the current collector layer covers the first active substance layer. And the current collector layer is arranged on one side, far away from the solid electrolyte layer, of the first active material layer. The composite pole piece provided by the invention aims to reduce the interface contact resistance, improve the fast charging performance of the battery and improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a composite pole piece and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries have a higher energy density and can store more energy in the same volume or weight, thereby increasing the range of new energy vehicles. A longer range can reduce the number and time of charging and improve the convenience of use. In addition, solid-state batteries are safer than liquid batteries. Since solid-state batteries do not use liquid electrolytes, they avoid safety issues such as leakage and combustion. This is crucial to the safety of new energy vehicles, especially during charging and use, solid-state batteries can provide better safety protection.

[0003] With the widespread application of solid-state batteries, the requirements for their performance have become increasingly stringent, such as requiring them to have fast charging capabilities. However, when the battery cell is a wound structure, the interface resistance between the solid electrolyte and the positive and negative electrodes during the fast charging process of the solid-state battery is large, resulting in increased energy loss and reduced battery cycle performance. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a composite pole piece and a preparation method thereof, and a solid-state battery. The composite pole piece provided in this application aims to reduce the interface contact resistance, improve the fast charging performance of the battery, and improve the cycle performance of the battery.

[0005] In the first aspect of the present invention, the present invention proposes a composite pole piece. According to an embodiment of the present invention, the composite pole piece includes a solid electrolyte layer, a first active material layer and a current collector layer. A plurality of holes are distributed on the surface of at least one side of the solid electrolyte layer. The first active material layer is arranged on one side of the solid electrolyte layer. The first active material layer covers the holes. The current collector layer is arranged on the side of the first active material layer away from the solid electrolyte layer.

[0006] According to the composite pole piece of the above embodiment of the present invention, the multiple holes distributed on the surface of the solid electrolyte layer can, on the one hand, increase the surface area of ​​the solid electrolyte, so that the active material layer can better cover and embed these pore structures, greatly increase the contact area between the solid electrolyte and the active material, and provide more channels for the transmission of electrons and ions, thereby effectively reducing the interface contact resistance between the solid electrolyte and the positive and negative electrodes, thereby reducing the obstacles in the ion migration process, so that the ions can move between the electrode and the electrolyte at a higher rate, thereby improving the fast charging performance of the battery. On the other hand, the holes can form a mechanical interlock between the active material layer and the solid electrolyte layer, improve the bonding strength between the two, and better maintain the stability of the ion channel during the cycle process, ensuring that ions can be continuously and stably transmitted between the electrode and the electrolyte, thereby improving the cycle performance of the battery. Therefore, the composite pole piece provided by the present application can reduce the interface contact resistance between the solid electrolyte and the positive and negative electrodes, improve the fast charging performance of the battery, and improve the cycle performance of the battery.

[0007] In addition, the composite pole piece according to the above embodiment of the present invention may also have the following additional technical features:

[0008] In some embodiments of the present invention, the pores have a diameter of 0.01 μm to 50 μm, which is beneficial for the rapid diffusion of ions and improves the fast charging performance of the battery.

[0009] In some embodiments of the present invention, the pores have a depth of 0.1 μm to 50 μm, thereby ensuring that there is enough space for active materials to be embedded, thereby providing more channels for the transmission of electrons and ions and reducing interface contact resistance.

[0010] In some embodiments of the present invention, the tensile strength of the solid electrolyte layer is 10MPa-2000MPa. Thus, the solid electrolyte layer has a relatively high strength, and the high-strength solid electrolyte layer is used as a matrix to provide a stable supporting structure for the battery.

[0011] In some embodiments of the present invention, the solid electrolyte layer has a puncture strength of 50 gf-2000 gf, thereby ensuring that the ion transmission channel in the solid electrolyte layer is not damaged, and maintaining good charge and discharge performance and cycle performance of the battery.

[0012] In some embodiments of the present invention, the thickness of the solid electrolyte layer is d1, 0.01 μm≤d1≤100 μm, preferably 1 μm≤d1≤30 μm. Thus, the migration path of ions in the solid electrolyte can be reduced, and the fast charging performance of the battery can be improved.

[0013] In some embodiments of the present invention, the width of the solid electrolyte layer is L1, 100 mm ≤ L1 ≤ 3000 mm, preferably 200 mm ≤ L1 ≤ 2000 mm. Thus, it can be conveniently combined with electrodes and current collectors of different sizes to construct a battery with a reasonable structure.

[0014] In some embodiments of the present invention, the solid electrolyte layer includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a polymer solid electrolyte and a composite solid electrolyte, preferably a sulfide solid electrolyte.

[0015] In some embodiments of the present invention, the thickness of the first active material layer is d2, 50 μm≤d2≤300 μm, preferably 60 μm≤d2≤270 μm. Thus, sufficient energy storage can be ensured while minimizing the obstruction of ion transmission.

[0016] In some embodiments of the present invention, the thickness of the current collector layer is d3, 1 μm ≤ d3 ≤ 20 μm, preferably 2 μm ≤ d3 ≤ 10 μm. Thus, the proportion of the current collector layer in the total mass of the battery can be reduced, so that more mass can be allocated to the active material, thereby increasing the energy storage capacity of the battery per unit mass, which is beneficial to improving the mass energy density of the battery.

[0017] In some embodiments of the present invention, the current collector layer includes one of a positive electrode current collector layer and a negative electrode current collector layer.

[0018] In some embodiments of the present invention, the positive electrode current collector layer includes aluminum nanoparticles.

[0019] In some embodiments of the present invention, the volume average particle size Dv50 of the aluminum nanoparticles is D1, 1nm≤D1≤20μm, preferably 10nm≤D1≤10μm. This is beneficial to improve the interface bonding between the positive electrode current collector layer and the active material, can prevent the active material from falling off during the charge and discharge process, and improve the cycle life of the battery.

[0020] In some embodiments of the present invention, the negative electrode current collector layer includes copper nanoparticles.

[0021] In some embodiments of the present invention, the volume average particle size Dv50 of the copper nanoparticles is D2, 1nm≤D2≤20μm, preferably 10nm≤D2≤10μm. This is beneficial to improve the interface bonding between the negative electrode current collector layer and the active material, can prevent the active material from falling off during the charge and discharge process, and improve the cycle life of the battery.

[0022] In some embodiments of the present invention, the composite pole piece further includes a second active material layer, which is disposed on a side of the current collector layer away from the first active material layer, and the material of the first active material layer is the same as the material of the second active material layer. Thus, the wound composite pole piece can be prepared conveniently.

[0023] In the second aspect of the present invention, a method for preparing the above-mentioned composite pole piece is proposed, the method comprising: preparing a solid electrolyte layer, performing a pore-forming treatment on the surface of at least one side of the solid electrolyte layer to form a plurality of holes on the surface of at least one side of the solid electrolyte layer; preparing a first active material layer on one side of the solid electrolyte layer, the first active material layer covering the holes; preparing a current collector layer on the side of the first active material layer away from the solid electrolyte layer to obtain a composite pole piece. Thus, the obtained composite pole piece can reduce the interface contact resistance between the solid electrolyte and the positive and negative electrodes, improve the fast charging performance of the battery, and improve the cycle performance of the battery.

[0024] In some embodiments of the present invention, the pore making method includes laser texturing, thereby the size, shape and distribution of the pores can be precisely controlled, the pore structure on the surface of the solid electrolyte layer can be customized, and pores with diameters at the micrometer or even nanometer level and uniform distribution can be manufactured.

[0025] In some embodiments of the present invention, the cutting power of the laser texturing is 50 W-500 W, preferably 80 W-300 W. Thus, the melting and vaporization degree of the solid electrolyte material can be accurately controlled, which is conducive to manufacturing a high-quality pore structure on the surface of the solid electrolyte layer.

[0026] In some embodiments of the present invention, the cutting speed of the laser texturing is 50 mm / s-2000 mm / s, preferably 100 mm / s-800 mm / s. Thus, the density and size of the pores on the surface of the solid electrolyte layer can be effectively adjusted, which helps to produce a uniform pore structure.

[0027] In some embodiments of the present invention, the steps of preparing the first active material layer and preparing the current collector layer include: preparing active material slurry; coating the active material slurry on one side of the solid electrolyte layer, dehydrating the active material slurry to obtain a first active material layer intermediate, so that the first active material layer intermediate covers the hole; spraying the raw material of the current collector layer on the side of the first active material layer intermediate away from the solid electrolyte layer, drying, so as to form the first active material layer on one side of the solid electrolyte layer and the current collector layer on the side of the first active material layer away from the solid electrolyte layer. Thus, it is beneficial to the rapid conduction of electrons between the active material layer and the current collector layer, reduce the contact resistance, and improve the charge and discharge efficiency of the battery.

[0028] In some embodiments of the present invention, the weight loss rate of the active material slurry is less than 80%. Thus, it can be ensured that the active material layer intermediate formed after the active material slurry is dehydrated has a certain humidity, so that a more compact, continuous and less defective contact interface is formed between the current collector layer and the active material, effectively reducing the interface contact resistance, accelerating the ion embedding and extraction of the electrode and the conduction speed of the electron in the circuit, so that the battery can complete the charging process in a shorter time, meet the needs of fast charging, and improve the fast charging performance of the battery.

[0029] In some embodiments of the present invention, the spraying method includes at least one of magnetron sputtering and vacuum evaporation.

[0030] In some embodiments of the present invention, the method for preparing a composite pole piece further includes: preparing a second active material layer on a side of the current collector layer away from the first active material layer, wherein the material of the first active material layer is the same as that of the second active material layer.

[0031] In the third aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present application, the solid-state battery includes the composite electrode sheet or the composite electrode sheet prepared by the above method. The solid-state battery has good fast charging performance and cycle performance.

[0032] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0034] Figure 1 A schematic diagram showing the structure of a composite pole piece according to an embodiment of the present invention is shown;

[0035] Figure 2 A left side view of a composite pole piece according to an embodiment of the present application is shown;

[0036] Figure 3 A schematic structural diagram of a composite pole piece according to another embodiment of the present application is shown.

[0037] Reference numerals: composite pole piece 10 , solid electrolyte layer 1 , first active material layer 2 , current collector layer 3 , second active material layer 4 . DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0039] With the increasing global awareness of environmental protection and the advancement of sustainable development, the development momentum of new energy is strong. However, with the widespread application of power batteries in various fields, there is still a need to further improve the energy density of current power batteries.

[0040] Solid-state batteries have a higher energy density, which means that they can store more energy in the same volume or weight, thereby increasing the range of new energy vehicles. A longer range can reduce the number and time of charging and improve the convenience of use. In addition, solid-state batteries are safer than liquid batteries. Since solid-state batteries do not use liquid electrolytes, they avoid safety issues such as leakage and combustion. This is crucial to the safety of new energy vehicles, especially during charging and use, solid-state batteries can provide better safety protection. The development of solid-state batteries is of great significance to the sustainable development of the new energy field. With the continuous advancement of technology and the continuous expansion of market demand, solid-state batteries are expected to become one of the mainstream battery technologies in the field of new energy vehicles in the future.

[0041] However, solid-state batteries currently also have technical difficulties such as interface contact. In addition, it is difficult to have a cost advantage in the short term, and there are still problems to be solved in processing and manufacturing, which has led to its failure to be widely used. In order to accelerate the large-scale application of solid-state batteries, focus should be placed on technical interface problems. The interface resistance between the solid electrolyte and the positive and negative electrodes is large, which will increase the energy loss of the battery during the charging and discharging process and reduce the efficiency of the battery. The formation of interface resistance is related to the difference in physical and chemical properties between the electrolyte and the positive and negative electrode materials. In order to improve the interface problems of solid-state batteries, the contact between the electrolyte and the positive and negative electrodes is usually improved by introducing a buffer layer, interface modification, etc. However, the above methods can only optimize the solid-solid contact interface, and it is difficult to significantly improve or solve the interface contact problem.

[0042] The composite pole piece disclosed in the embodiment of the present application is suitable for solid-state batteries, and the solid-state battery disclosed in the embodiment of the present application can be used in electrical equipment using batteries as power sources or various energy storage systems using batteries as energy storage elements. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0043] The first aspect of the present invention provides a composite pole piece 10, referring to Figure 1 According to an embodiment of the present invention, the composite pole piece 10 includes a solid electrolyte layer 1, a first active material layer 2 and a current collector layer 3, a plurality of holes are distributed on the surface of at least one side of the solid electrolyte layer 1, the first active material layer 2 is arranged on one side of the solid electrolyte layer 1, the first active material layer 2 covers the holes, and the current collector layer 3 is arranged on the side of the first active material layer 2 away from the solid electrolyte layer 1.

[0044] According to the composite pole piece 10 of the embodiment of the present invention, the multiple pore structures distributed on the surface of the solid electrolyte layer 1 can, on the one hand, increase the surface area of ​​the solid electrolyte, so that the first active material layer 2 can better cover and embed these pore structures, greatly increase the contact area between the solid electrolyte and the active material, and provide more channels for the transmission of electrons and ions, thereby effectively reducing the interface contact resistance between the solid electrolyte and the positive and negative electrodes, thereby reducing the obstacles in the ion migration process, so that the ions can move between the electrode and the electrolyte at a higher rate, thereby improving the fast charging performance of the battery. On the other hand, the pore structure can form a mechanical interlock between the active material layer and the solid electrolyte layer 1, improve the bonding strength between the two, and better maintain the stability of the ion channel during the cycle process, ensuring that the ions can be continuously and stably transmitted between the electrode and the electrolyte, thereby improving the cycle performance of the battery. Therefore, the composite pole piece 10 provided in the present application can reduce the interface contact resistance between the solid electrolyte and the positive and negative electrodes, improve the fast charging performance of the battery, and improve the cycle performance of the battery.

[0045] In some embodiments of the present application, the pore size is 0.01 μm-50 μm. For example, it can be 0.01 μm, 0.1 μm, 1 μm, 10 μm, 50 μm, etc. During the fast charging process of the battery, a large number of lithium ions need to pass through the solid electrolyte layer 1 quickly. By limiting the depth of the pores within the above range, the ion transmission path can be shortened, which is conducive to the rapid diffusion of ions and improves the fast charging performance of the battery. It can also ensure that there is enough space for the active material layer to form an effective mechanical interlock with the solid electrolyte layer 1, thereby increasing the bonding strength between the two and improving the cycle performance of the battery.

[0046] In the present application, “pore size” refers to the diameter of the pores distributed on the surface of the solid electrolyte layer 1 . The present application uses a crystal phase microscope to test the pore size of the pores on the surface of the solid electrolyte layer 1 .

[0047] In some embodiments of the present application, the pore depth is 0.1 μm-50 μm. For example, it can be 0.1 μm, 1 μm, 5 μm, 10 μm, 50 μm, etc. By limiting the pore depth within the above range, on the one hand, the contact area between the solid electrolyte and the active material can be increased, and the active material is filled in the pore depth direction to shorten the lithium ion shuttle path and reduce the interface contact resistance. On the other hand, different degrees of pores can better contact with the active material, firmly fix the active material in the solid electrolyte layer 1, and improve the bonding strength between the two, thereby improving the cycle performance of the battery.

[0048] In the present application, “pore depth” refers to the depth of the pores distributed on the surface of the solid electrolyte layer 1 in a direction perpendicular to the surface of the solid electrolyte layer 1 . The present application uses a crystal phase microscope to test the pore size of the pores on the surface of the solid electrolyte layer 1 .

[0049] In some embodiments of the present application, the tensile strength of the solid electrolyte layer 1 is 10MPa-2000MPa. For example, it can be 10MPa, 100MPa, 500MPa, 1000MPa, 1500MPa, 2000MPa, etc. By limiting the tensile strength of the solid electrolyte layer 1 to the above range, the solid electrolyte layer has a higher strength, and the high-strength solid electrolyte layer 1 is used as a matrix to provide a stable support structure for the battery. When the positive and negative electrode slurries are directly coated on the solid electrolyte matrix, the micropores of different sizes on the solid electrolyte layer can make the active material more firmly combined, and can still fit tightly when the volume of the electrode material changes, maintain good electrical contact, reduce interface resistance, and improve the charge and discharge efficiency of the battery.

[0050] In some embodiments of the present application, the puncture strength of the solid electrolyte layer 1 is 50gf-2000gf. For example, it can be 50gf, 100gf, 500gf, 1000gf, 1500gf, 2000gf, etc. By limiting the puncture strength of the solid electrolyte layer 1 to the above range, it can be ensured that the transmission channel of ions in the solid electrolyte layer 1 is not destroyed, and the good charge and discharge performance and cycle performance of the battery are maintained.

[0051] In some embodiments of the present application, the thickness of the solid electrolyte layer 1 is d1, 0.01μm≤d1≤100μm. For example, it can be 0.01μm, 1μm, 10μm, 50μm, 100μm, etc. By limiting the thickness of the solid electrolyte layer 1 to the above range, the migration path of ions in the solid electrolyte can be reduced. During the charging process, the distance that lithium ions move from the positive electrode to the negative electrode is reduced, and they can reach the negative electrode faster, thereby improving the fast charging performance of the battery. In other embodiments of the present application, the thickness of the solid electrolyte layer 1 is preferably 1μm-30μm.

[0052] In some embodiments of the present application, reference Figure 2 , the width of the solid electrolyte layer 1 is L1, 100mm≤L1≤3000mm. For example, it can be 100mm, 500mm, 1000mm, 2000mm, 3000mm. By limiting the width of the solid electrolyte layer 1 to the above range, it can be conveniently combined with electrodes and current collectors of different sizes to construct a battery with a reasonable structure. In other embodiments of the present application, the width of the solid electrolyte layer 1 is preferably 200mm≤L1≤2000mm.

[0053] In some embodiments of the present application, the present application has no specific restrictions on the type of solid electrolyte layer 1, which can be selected according to needs. For example, the solid electrolyte layer 1 includes but is not limited to at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a polymer solid electrolyte, and a composite solid electrolyte. In other embodiments of the present application, the solid electrolyte layer 1 includes a sulfide solid electrolyte.

[0054] In some embodiments of the present application, the thickness of the first active material layer 2 is d2, 50μm≤d2≤300μm. For example, it can be 50μm, 100μm, 150μm, 200μm, 300μm, etc. By limiting the thickness of the first active material layer 2 to the above range, it is possible to minimize the obstruction of ion transmission while ensuring sufficient energy storage. In other embodiments of the present application, the thickness of the active material layer is preferably 60μm≤d2≤270μm.

[0055] In some embodiments of the present application, the active material layer includes one of a positive electrode active material layer and a negative electrode active material layer.

[0056] In some embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material for a battery known in the art. As an example, the positive electrode active material can include at least one of the following materials: a lithium-containing phosphate, a lithium transition metal oxide, and their respective modified compounds.

[0057] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0058] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0059] In some embodiments of the present application, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material can be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material can include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and titanates.

[0060] In some embodiments of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS).

[0061] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0062] In some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).

[0063] In some embodiments of the present application, the thickness of the current collector layer 3 is d3, 1μm≤d3≤20μm. For example, it can be 1μm, 5μm, 10μm, 15μm, 20μm, etc. By limiting the thickness of the current collector layer 3 to the above range, the proportion of the current collector layer 3 in the total mass of the battery can be reduced, so that more mass can be allocated to the active material, thereby increasing the energy storage capacity of the battery per unit mass, which is beneficial to improving the mass energy density of the battery. In other embodiments of the present application, the thickness of the current collector layer 3 is preferably 2μm≤d3≤10μm.

[0064] As an example, the current collector layer 3 includes one of a positive electrode current collector layer and a negative electrode current collector layer.

[0065] As an example, the positive electrode current collector layer includes aluminum nanoparticles.

[0066] In some embodiments of the present application, the volume average particle size Dv50 of the aluminum nanoparticles is D1, 1nm≤D1≤20μm. For example, it can be 1nm, 100nm, 1μm, 5μm, 15μm, 20μm, etc. By limiting the volume average particle size of the aluminum nanoparticles to the above range, the aluminum nanoparticles can be better filled in the gaps between the active material particles to form a close contact, which is beneficial to improve the interface bonding between the positive electrode current collector layer and the active material, and can prevent the active material from falling off during the charge and discharge process, thereby improving the cycle life of the battery. In other embodiments of the present application, the volume average particle size Dv50 of the aluminum nanoparticles is preferably 10nm≤D1≤10μm.

[0067] In the present application, the volume average particle size Dv50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%. The test method of the volume average particle size Dv50 of aluminum nanoparticles refers to the standard GB / T 19077-2016, and the volume average particle size Dv50 of aluminum nanoparticles is tested using a laser particle size analyzer (such as Malvern Master Size3000).

[0068] As an example, the negative electrode current collector layer includes copper nanoparticles.

[0069] In some embodiments of the present application, the volume average particle size Dv50 of the copper nanoparticles is D2, 1nm≤D2≤20μm. For example, it can be 1nm, 100nm, 1μm, 5μm, 15μm, 20μm, etc. By limiting the volume average particle size of the copper nanoparticles to the above range, the copper nanoparticles can be better filled in the gaps between the active material particles to form a close contact, which is beneficial to improve the interface bonding between the negative electrode current collector layer and the active material, and can prevent the active material from falling off during the charge and discharge process, thereby improving the cycle life of the battery. In other embodiments of the present application, the volume average particle size Dv50 of the copper nanoparticles is preferably 10nm≤D1≤10μm.

[0070] In some embodiments of the present application, reference Figure 3 The composite pole piece 10 further includes a second active material layer 4, which is disposed on a side of the current collector layer away from the first active material layer 2, and the material of the first active material layer 2 is the same as the material of the second active material layer 4. Thus, the wound composite pole piece 10 is conveniently prepared.

[0071] A second aspect of the present invention provides a method for preparing the above-mentioned composite pole piece. According to an embodiment of the present invention, the method comprises:

[0072] S1. Prepare a solid electrolyte layer, and perform pore-forming treatment on the surface of at least one side of the solid electrolyte layer to form a plurality of pores on the surface of at least one side of the solid electrolyte layer.

[0073] In this step, by preparing a solid electrolyte layer and performing a pore-forming treatment on the surface of at least one side of the solid electrolyte layer, a plurality of holes can be formed on the surface of at least one side of the solid electrolyte layer. The multiple holes distributed on the surface of the solid electrolyte layer can, on the one hand, increase the surface area of ​​the solid electrolyte, so that the active material layer can better cover and embed these pore structures, greatly increase the contact area between the solid electrolyte and the active material, and provide more channels for the transmission of electrons and ions, thereby effectively reducing the interface contact resistance between the solid electrolyte and the positive and negative electrodes, thereby reducing the obstacles in the ion migration process, so that the ions can move between the electrode and the electrolyte at a higher rate, thereby improving the fast charging performance of the battery. On the other hand, the hole can form a mechanical interlock between the active material layer and the solid electrolyte layer, improve the bonding strength between the two, better maintain the stability of the ion channel during the cycle, and ensure that the ions can be continuously and stably transmitted between the electrode and the electrolyte, thereby improving the cycle performance of the battery. Thus, the composite pole piece provided by the present application can reduce the interface contact resistance between the solid electrolyte and the positive and negative electrodes, improve the fast charging performance of the battery, and improve the cycle performance of the battery.

[0074] In some embodiments of the present application, the method for making holes is not particularly limited, and those skilled in the art can flexibly select according to needs. In a specific embodiment of the present application, the method for making holes includes laser texturing. Laser texturing technology can accurately control the size, shape and distribution of holes, can achieve customization of the pore structure on the surface of the solid electrolyte layer, and can produce holes with diameters at the micrometer or even nanometer level and uniform distribution.

[0075] It should be noted that laser texturing refers to a processing technology that uses a high-energy-density laser beam to interact with the surface of a material. When the laser beam is focused on the surface of the solid electrolyte layer, the material absorbs the energy of the laser, causing the surface temperature to rise sharply. Due to the high concentration of laser energy, local areas on the surface of the material will quickly reach the melting point or even the boiling point. For solid electrolyte materials, such as oxide ceramics or polymer electrolytes, the movement of atoms on their surface intensifies under the action of laser energy. When the energy is high enough, the atoms or molecules on the surface of the material will be vaporized or melted to form tiny pits or holes. At the same time, during the laser action process, some areas around the material may undergo microstructural changes due to heat conduction, such as recrystallization, which further affects the roughness and pore structure of the material surface.

[0076] In some embodiments of the present application, the cutting power of the laser texturing is 50W-500W. For example, it can be 50W, 100W, 200W, 500W, etc. By limiting the cutting power of the laser texturing within the above range, the laser texturing surface pores of the solid electrolyte material can be accurately controlled, which is conducive to manufacturing a structure with controllable surface pores on the surface of the solid electrolyte layer. In other embodiments of the present application, the cutting power of the laser texturing is preferably 80W-300W.

[0077] In some embodiments of the present application, the cutting speed of the laser texturing is 50 mm / s-2000 mm / s. For example, it can be 50 mm / s, 100 mm / s, 1000 mm / s, 2000 mm / s, etc. By limiting the cutting speed of the laser texturing within the above range, the density and size of the pores on the surface of the solid electrolyte layer can be effectively adjusted, which helps to produce a uniform pore structure. In other embodiments of the present application, the cutting speed of the laser texturing is preferably 100 mm / s-800 mm / s.

[0078] S2. Prepare a first active material layer on one side of the solid electrolyte layer, wherein the first active material layer covers the holes.

[0079] In this step, the first active material layer is prepared on one side of the solid electrolyte layer so that the first active material layer can cover the pore structure. The first active material layer covers the pore structure, which can enhance the mechanical bonding force between the active material and the solid electrolyte. The active material particles can be partially embedded in the pores to form a structure similar to mechanical interlocking, making the interface between the two closer, which can effectively prevent the active material from falling off the surface of the solid electrolyte layer, maintain the stability of the interface, reduce the increase in resistance caused by interface problems, and thus extend the cycle life of the battery.

[0080] In some embodiments of the present application, the first active material layer can be prepared in the following manner: the active material slurry is coated on one side of the solid electrolyte layer having multiple pore structures, and after drying, the first active material layer can be formed on one side of the solid electrolyte layer so that the active material layer can cover the pore structure.

[0081] In some embodiments of the present application, the active material slurry includes positive electrode active material slurry or negative electrode active material slurry.

[0082] S3. Prepare a current collector layer on a side of the first active material layer away from the solid electrolyte layer to obtain a composite electrode.

[0083] In this step, a current collector layer is prepared on a side of the first active material layer away from the solid electrolyte layer to obtain a composite electrode.

[0084] In some embodiments of the present application, the current collector layer can be prepared by the following method: spraying the raw material of the current collector layer (such as aluminum nanoparticles or copper nanoparticles, etc.) onto one side of the active material layer by vacuum sputtering or the like to form the current collector layer.

[0085] In some embodiments of the present application, the steps of preparing a first active material layer and preparing a current collector layer include: preparing an active material slurry; coating the active material slurry on one side of the solid electrolyte layer, and performing a dehydration treatment to obtain an active material layer intermediate, so that the first active material layer intermediate covers the hole; spraying the raw material of the current collector layer on the side of the first active material layer intermediate away from the solid electrolyte layer, and drying to form a first active material layer on one side of the solid electrolyte layer and a current collector layer on the side of the first active material layer away from the solid electrolyte layer.

[0086] In this step, by directly applying the active material slurry to the surface of the solid electrolyte layer, the original solid-solid contact between the solid electrolyte layer and the active material layer is changed to solid-liquid contact, so that the active material can be more evenly distributed on one side of the solid electrolyte layer. During the coating process, the slurry can fully fill the pore structure on the surface of the solid electrolyte layer, and the first active material layer intermediate formed after the dehydration treatment can cover these holes well, so that the first active material layer can be better attached to the solid electrolyte layer, which can improve the cycle life and stability of the battery. Further spraying the raw material of the current collector layer directly on the first active material layer intermediate, and then drying, the current collector layer and the first active material layer can form a tight binding structure, which is conducive to the rapid conduction of electrons between the active material layer and the current collector layer, reducing the contact resistance, and improving the charge and discharge efficiency of the battery.

[0087] In some embodiments of the present application, the weight loss rate of the active material slurry is less than 80%. For example, it can be 1%, 10%, 20%, 40%, 60%, 79%, etc. By limiting the weight loss rate of the active material slurry within the above range, it can be ensured that the active material layer intermediate formed after the active material slurry is dehydrated has a certain humidity. When the raw material of the current collector layer is sprayed on the side of the first active material layer intermediate away from the solid electrolyte layer, the current collector layer and the first active material layer are in gas-liquid contact when they first contact, which changes the solid-liquid contact mode between the traditional foil and the active material slurry. This gas-liquid contact enables the vaporized powder to be more evenly dispersed in the active material slurry, and in the subsequent drying process, a more compact, continuous and less defective contact interface is formed with the active material. For example, nano-aluminum and nano-copper powders can be filled into the gaps between slurry particles to enhance the mutual bonding force, reduce the resistance increase factors that may appear at the interface, effectively reduce the interface contact resistance, accelerate the ion embedding and extraction of electrodes and the conduction speed of electrons in the circuit, so that the battery can complete the charging process in a shorter time, meet the needs of fast charging, and improve the fast charging performance of the battery.

[0088] In the present application, "weight loss rate" refers to the ratio of the mass lost by the active material slurry after dehydration to the original mass. In fact, it is mainly due to the loss of water during the dehydration process, which leads to a decrease in the weight of the active material slurry coated on the solid electrolyte layer. The calculation formula is: weight loss rate = (original mass - remaining mass) / original mass × 100%.

[0089] In the present application, there is no particular limitation on the spraying method, and those skilled in the art can flexibly select it according to needs. As an example, the spraying method includes at least one of magnetron sputtering and vacuum evaporation.

[0090] In some embodiments of the present application, the method for preparing a composite electrode also includes preparing a second active material layer on a side of the current collector layer away from the first active material layer. Specifically, the active material slurry is coated on a side of the current collector layer that has not been completely dried and away from the first active material layer, so that the initial contact between the current collector layer and the second active material layer is also liquid-liquid contact. The flow properties of the liquid can be used to better fuse the current collector layer and the second active material layer to form a better contact interface, which can reduce possible gaps or defects at the interface, ensure that electrons can be smoothly conducted between the two layers, effectively reduce the contact resistance, and improve the conductivity of the battery.

[0091] According to the preparation method of the embodiment of the present application, laser roughening is used to perform pore formation treatment on the surface of the solid electrolyte layer to form a plurality of pore structures on one side of the surface of the solid electrolyte layer, which can increase the surface area of ​​the solid electrolyte layer. When the active material slurry is coated on the solid electrolyte layer substrate, the liquid slurry can rely on its own fluidity to better fill the pores and other microstructures on the surface of the solid electrolyte caused by laser roughening, so that a tightly fitting and large-area contact interface is formed between the active material and the solid electrolyte, which greatly increases the effective channel for ion transmission, thereby significantly reducing the interface contact impedance and ensuring smoother migration of ions between the electrode and the electrolyte.

[0092] Furthermore, by using a specific method (such as vacuum construction spraying of nano-aluminum to the positive electrode coating surface, magnetron sputtering of nano-copper to the negative electrode coating surface) to contact the vaporized powder with the active material slurry before the active material slurry is completely dried, a gas-liquid contact is formed, which changes the solid-liquid contact mode between the traditional foil and the active material slurry. This gas-liquid contact enables the vaporized powder to be more evenly dispersed in the active material slurry, and in the subsequent drying process, a tighter, continuous and less defective contact interface is formed with the active material. For example, nano-aluminum and nano-copper powders can be filled into the gaps between the slurry particles, enhance the mutual bonding force, reduce the resistance increase factors that may appear at the interface, effectively reduce the interface contact resistance, speed up the ion embedding and extraction of the electrode and the conduction speed of the electron in the circuit, so that the battery can complete the charging process in a shorter time, meet the needs of fast charging, and improve the fast charging performance of the battery.

[0093] The third aspect of the present invention provides a solid-state battery. According to an embodiment of the present application, the solid-state battery includes the composite electrode sheet or the composite electrode sheet prepared by the method described above. The solid-state battery has good fast charging performance and cycle performance.

[0094] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.

[0095] Example 1

[0096] 1) preparing a sulfide solid electrolyte, performing laser texturing on the surface of the sulfide solid electrolyte layer, forming a plurality of pore structures on the surface of the sulfide solid electrolyte layer, and obtaining a sulfide solid electrolyte layer having a plurality of pore structures distributed on the surface, wherein the laser power of the laser texturing is 50 W, the cutting speed of the laser texturing is 600 mm / s, the pore diameter is 25 μm, the pore depth is 15 μm, the tensile strength is 1500 MPa, the needle puncture strength is 1000 gf, the thickness of the sulfide solid electrolyte layer is 20 μm, and the width of the solid electrolyte layer is L1=500 mm;

[0097] 2) The positive electrode active material is lithium nickel cobalt manganese oxide (NCM523, i.e. LiNi 0.5 Co 0.2 Mn 0.3 O2), binder polyvinylidene fluoride PVDF, conductive agent acetylene black (Super P), dielectric material particles barium titanate are mixed in a weight ratio of 98:1:1:0, N-methylpyrrolidone (NMP) is added as a solvent, and the slurry is stirred in a vacuum state until it is uniform to obtain a positive electrode active material slurry; the negative electrode active material artificial graphite, conductive agent acetylene black, composite binder SBR (styrene butadiene rubber), and dispersant sodium carboxymethyl cellulose (CMC-Na) are dissolved in solvent deionized water in a weight ratio of 94:1:1:1, and stirred and mixed uniformly to prepare a negative electrode active slurry; the positive electrode active material slurry is coated on one side of the solid electrolyte layer obtained in step 1), and the negative electrode active material slurry is coated on the other side of the solid electrolyte layer obtained in step 1), and then dehydrated to obtain a first positive electrode active material layer intermediate after the weight loss rate of the positive electrode active material slurry is 50%, and the first negative electrode active material layer intermediate after the weight loss rate of the negative electrode active material slurry is 50%;

[0098] 3) spraying aluminum nanomaterials on the side of the first positive active material layer intermediate obtained in step 2) away from the solid electrolyte layer by magnetron sputtering to obtain a positive current collector layer; spraying copper nanomaterials on the side of the first negative active material layer intermediate obtained in step 2) away from the solid electrolyte layer by vacuum evaporation to obtain a negative current collector layer; wherein the thickness of the positive current collector layer is 12 μm, the thickness of the negative current collector layer is 12 μm, the volume average particle size Dv50 of the aluminum nanoparticles is 1 μm, and the volume average particle size Dv50 of the copper nanoparticles is 3 μm;

[0099] 4) coating the positive electrode active material slurry in step 2) on the positive electrode current collector layer obtained in step 3) to obtain a second positive electrode active material layer; coating the negative electrode active material slurry in step 2) on the negative electrode current collector layer obtained in step 3) to obtain a second negative electrode active material layer, drying the obtained composite electrode sheet, the first positive electrode active material layer intermediate becomes the first positive electrode active material layer, and the first negative electrode active material layer intermediate becomes the first negative electrode active material layer, wherein the thickness of the first positive electrode active material layer is 80 μm, and the thickness of the first negative electrode active material layer is 80 μm, and finally assembling to obtain a solid-state battery.

[0100] During the preparation process of the solid-state batteries of Examples 2-29 and Comparative Example 1, except for some experimental parameters being different (see Table 1), the rest are the same as in Example 1.

[0101] Some parameters of the solid-state batteries of Examples 1-29 and Comparative Example 1 are shown in Table 1.

[0102] Table 1

[0103]

[0104] “ / ” means none.

[0105] Comparative Example 2

[0106] The composition and proportion of the raw materials used in Comparative Example 2 are the same as those in Example 1, except that the process of preparing the electrode is different, specifically including:

[0107] 1) Prepare positive electrode active material slurry and negative electrode active material slurry respectively according to the method of Example 1, take the negative electrode active material slurry, wherein the negative electrode active material has the same coating surface density parameters as in Example 1, and apply it on a copper foil with a thickness of 6 μm; take the positive electrode active material slurry, wherein the positive electrode active material has the same coating surface density parameters as in Experimental Example 1, and apply it on an aluminum foil with a thickness of 12 μm.

[0108] 2) The coated electrode sheets are wound to prepare positive electrode sheets and negative electrode sheets.

[0109] 3) Obtain a solid-state battery through conventional assembly and other processes.

[0110] Testing and analysis

[0111] Under the same conditions, the solid-state batteries of Examples 1-29 and Comparative Examples 1-2 were tested for electrode resistivity, internal resistance, and cycle capacity retention, respectively. The specific testing methods are as follows:

[0112] Pole sheet resistivity: Take the pole sheet after each batch of test rolling, the pole sheet size is 10cm long * 10cm wide. Open the pole sheet resistivity test software, measure the single-sided thickness of the pole sheet and the thickness of the foil, and enter the thickness of the dressing layer and the thickness of the current collector respectively. If it is aluminum foil, select the volume resistivity of the current collector as 2.7000E-06, if it is copper foil, select 1.7000E-06. Record the test results.

[0113] Internal resistance: Different batches of batteries are tested using the battery HPPC test method and the test results are recorded. The specific test steps are shown in Table 2 below:

[0114] Table 2

[0115]

[0116]

[0117] “ / ” means none.

[0118] Cycle capacity retention rate: Cycle test conditions are shown in Table 3 below:

[0119] Table 3

[0120] Step Steps Working Mode Ambient temperature Sampling interval 1 Stand Rest 30min; 25℃ 30s 2 Constant current discharge 1C constant current discharge to 2.5V 25℃ 1s 3 Stand Rest 30min; 25℃ 30s 4 Constant current charging Charge at 1C rate to 4.25V; 25℃ 1s 5 Stand Rest 30min; 25℃ 30s 6 Constant current discharge 1C5 constant current discharge to 2.5V 25℃ 1s 6 / Repeat steps 3 to 6 up to 200 times / / 7 Finish / / /

[0121] “ / ” means none.

[0122] The capacity retention rate can be calculated by the battery capacity after 200 cycles: the capacity retention rate after 200 cycles = (discharge capacity of the 200th cycle / discharge capacity of the first cycle) × 100%. The test results are shown in Table 4.

[0123] Table 4

[0124]

[0125] Combining Table 1 and Table 4, it can be obtained that compared with the solid-state batteries of Comparative Examples 1-2, the electrode resistivity and internal resistance in the solid-state batteries of Examples 1-29 are lower, and the capacity retention rate is higher after 200 cycles under 1C / 1C conditions. The solid-state batteries of Examples 1-29 have both good fast charging performance and cycle performance. This is because the solid-state batteries of Examples 1-29 are prepared using the composite electrode provided by the present application, wherein a plurality of holes are distributed on the surface of the solid electrolyte layer, which can increase the surface area of ​​the solid electrolyte on the one hand, so that the active material layer can better cover and embed these pore structures, greatly increasing the contact area between the solid electrolyte and the active material, and providing more channels for the transmission of electrons and ions, thereby effectively reducing the interface contact resistance between the solid electrolyte and the positive and negative electrodes, thereby reducing the obstacles in the ion migration process, allowing ions to move between the electrode and the electrolyte at a higher rate, thereby improving the fast charging performance of the battery. On the other hand, the pores can form a mechanical interlock between the active material layer and the solid electrolyte layer, thereby increasing the bonding strength between the two and better maintaining the stability of the ion channel during the cycle, ensuring that ions can be continuously and stably transmitted between the electrode and the electrolyte, thereby improving the cycle performance of the battery.

[0126] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite pole piece, characterized in that: include: A solid electrolyte layer, wherein a plurality of holes are distributed on at least one side of the surface of the solid electrolyte layer; A first active material layer, disposed on one side of the solid electrolyte layer, the first active material layer covering the hole; The current collector layer is disposed on a side of the first active material layer away from the solid electrolyte layer.

2. The composite pole piece according to claim 1, characterized in that: The pores have a pore size of 0.01 μm-50 μm; And / or, the pore depth is 0.1 μm-50 μm; And / or, the tensile strength of the solid electrolyte layer is 10MPa-2000MPa; and / or, the solid electrolyte layer has a puncture strength of 50 gf-2000 gf; and / or, the thickness of the solid electrolyte layer is d1, 0.01 μm≤d1≤100 μm, preferably 1 μm≤d1≤30 μm; and / or, the width of the solid electrolyte layer is L1, 100 mm ≤ L1 ≤ 3000 mm, preferably 200 mm ≤ L1 ≤ 2000 mm; And / or, the solid electrolyte layer includes at least one of an oxide solid electrolyte, a sulfide solid electrolyte, a polymer solid electrolyte and a composite solid electrolyte, preferably a sulfide solid electrolyte.

3. The composite pole piece according to claim 1, characterized in that: The thickness of the first active material layer is d2, 50 μm≤d2≤300 μm, preferably 60 μm≤d2≤270 μm; and / or, the thickness of the current collector layer is d3, 1 μm≤d3≤20 μm, preferably 2 μm≤d3≤10 μm; And / or, the current collector layer includes one of a positive electrode current collector layer and a negative electrode current collector layer; and / or, the positive electrode current collector layer comprises aluminum nanoparticles; and / or, the volume average particle size Dv50 of the aluminum nanoparticles is D1, 1nm≤D1≤20μm, preferably 10nm≤D1≤10μm; and / or, the negative electrode current collector layer comprises copper nanoparticles; And / or, the volume average particle size Dv50 of the copper nanoparticles is D2, 1nm≤D2≤20μm, preferably 10nm≤D2≤10μm.

4. The composite pole piece according to any one of claims 1 to 3, characterized in that: The composite electrode further includes a second active material layer, which is disposed on a side of the current collector layer away from the first active material layer, and the material of the first active material layer is the same as that of the second active material layer.

5. A method for preparing the composite pole piece according to any one of claims 1 to 4, characterized in that: include: preparing a solid electrolyte layer, and performing a pore-forming treatment on a surface of at least one side of the solid electrolyte layer to form a plurality of pores on the surface of at least one side of the solid electrolyte layer; Prepare a first active material layer on one side of the solid electrolyte layer, wherein the first active material layer covers the pores; A current collector layer is prepared on a side of the first active material layer away from the solid electrolyte layer to obtain a composite electrode.

6. The method according to claim 5, characterized in that The method of making holes includes laser texturing; And / or, the cutting power of the laser texturing is 50W-500W, preferably 80W-300W; And / or, the cutting speed of the laser texturing is 50 mm / s-2000 mm / s, preferably 100 mm / s-800 mm / s.

7. The method according to claim 5, characterized in that The steps of preparing the first active material layer and preparing the current collector layer include: preparing an active substance slurry; Applying active material slurry on one side of the solid electrolyte layer and performing dehydration treatment to obtain a first active material layer intermediate, so that the first active material layer intermediate covers the pores; The raw material of the current collector layer is sprayed on the side of the first active material layer intermediate away from the solid electrolyte layer, and dried to form the first active material layer on one side of the solid electrolyte layer and the current collector layer on the side of the first active material layer away from the solid electrolyte layer.

8. The method according to claim 7, characterized in that The weight loss rate of the active material slurry is less than 80%; And / or, the spraying method includes at least one of magnetron sputtering and vacuum evaporation.

9. The method according to any one of claims 5 to 8, characterized in that: The method for preparing a composite electrode sheet further includes: preparing a second active material layer on a side of the current collector layer away from the first active material layer, wherein the material of the first active material layer is the same as that of the second active material layer.

10. A solid-state battery, characterized in that: A composite pole piece comprising any one of claims 1-4 or a composite pole piece obtained by the method of any one of claims 5-9.